pointblue/gdr_molt_sic: Schmidt et al. 2023 Sea ice concentration decline. Final - Annie Schmidt (Zenodo, 2023)
Final version of code used for analysis in Schmidt et al. 2023 Sea ice concentration decline in an important Adelie penguin molt area. PNAS.